2006
DOI: 10.4319/lo.2006.51.1.0339
|View full text |Cite
|
Sign up to set email alerts
|

External control of bacterial community structure in lakes

Abstract: Abstract-We investigated the importance of a regional factor for bacterial communities in lakes. External factors dominated the control of community structures in lakes with retention times up to 200 d, most likely as a result of bacterial import. Because these lakes are numerous in the boreal zone, regional processes can be of great importance for bacterial communities in general. Consequently, we propose that lakes function more like flow through systems, as opposed to the classical ''lake as microcosm '' co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 15 publications
4
116
0
3
Order By: Relevance
“…Previous studies have shown that the bacterial community composition strongly depends on the physicochemical conditions of the environment (Lindströ m, 2000; Yannarell and Triplett, 2004;Lindströ m et al, 2006b), interspecific interactions (Pernthaler et al, 2004;Schwalbach et al, 2005;Kent et al, 2006), available resources (Pinhassi et al, 1999;van Hannen et al, 1999;Crump et al, 2003;Newton et al, 2006) and dispersal (Curtis and Sloan, 2004;Langenheder et al, 2006;Lindströ m et al, 2006a). However, in none of these studies were there any attempts to predict bacterial distribution patterns from nonbacterial parameters.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have shown that the bacterial community composition strongly depends on the physicochemical conditions of the environment (Lindströ m, 2000; Yannarell and Triplett, 2004;Lindströ m et al, 2006b), interspecific interactions (Pernthaler et al, 2004;Schwalbach et al, 2005;Kent et al, 2006), available resources (Pinhassi et al, 1999;van Hannen et al, 1999;Crump et al, 2003;Newton et al, 2006) and dispersal (Curtis and Sloan, 2004;Langenheder et al, 2006;Lindströ m et al, 2006a). However, in none of these studies were there any attempts to predict bacterial distribution patterns from nonbacterial parameters.…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that bacterial communities can be assembled by species sorting (Beisner et al, 2006;Van der Gucht et al, 2007;Logue and Lindströ m, 2010) as well as mass effects (Lindströ m et al, 2006;Crump et al, 2007). It has also been demonstrated that frequency and abundance distributions in bacterial communities are, and often to a considerable extend, consistent with the neutral model (Sloan et al, 2006;Woodcock et al, 2007;Drakare and Liess, 2010;Ö stman et al, 2010).…”
Section: Introductionmentioning
confidence: 79%
“…For example, Ofiteru et al (2010) studied communities in wastewater treatment plants that are subject to high dispersal rates, and found that deterministic selection had little influence on microbial community composition, and was instead driven by neutral dynamics (drift and random immigration). In lakes, high immigration rates rarely overwhelm local selection (Jones and McMahon, 2009;Logue and Lindström, 2010) but can cause local communities to become more similar to the composition of communities immigrating (for example, from a stream inlet) (Lindström et al, 2006;Crump et al, 2007;Adams et al, 2014). Our results suggest that microbial growth rates are fast enough to observe strong deterministic effects in leaf litter communities even under extremely high Figure 5 Within-group distance (1 − Bray-Curtis similarity) of replicate communities within lignin/N treatments (x axis) that were exposed to different dispersal rates for 6 years (panels).…”
Section: Discussionmentioning
confidence: 99%